Green tea extract treatment alleviates ocular inflammation in a rat model of endotoxin-induced uveitis. - Yong Jie Qin (Public Library of Science (PLoS), 2014)
Green tea extract (GTE) ingested by rats exerted anti-oxidative activities in various ocular tissues as shown in our previous studies. The present work investigated anti-inflammatory effects of GTE on endotoxin-induced uveitis (EIU). EIU was generated in adult rats by a footpad injection of 1 mg/kg lipopolysaccharide (LPS). Oral administration of GTE (550 mg/kg) was given one, two or four times after LPS injection. Twenty-four hours later, LPS produced severe hyperemia and edema in the iris. Immunocytochemical examinations showed an accumulation of infiltrating cells in the aqueous humor that were immunopositive for cluster of differentiation 43 (CD43) and CD68, markers for leucocytes and macrophages, respectively. Analyses of the aqueous humor showed an increase in pro-inflammatory mediators including tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6) and monocyte chemoattractant protein-1 (MCP-1). GTE treatments improved the clinical manifestations and reduced infiltrating cells and protein exudation in the aqueous humor, which were not observed under half dose of GTE (275 mg/kg). The number of CD68 positive macrophages residing in the iris and ciliary was also reduced. GTE suppressed production of TNF-α, IL-6 and MCP-1 in the aqueous humor, which was associated with a down-regulation of LPS receptor complex subunits, Toll-like receptor 4 (TLR-4) and CD14, and suppression of nuclear factor-kappa Bp65 (NF-κBp65) in the iris and ciliary body. Our findings show that GTE is a potent anti-inflammatory agent against the inflammation of EIU, and suggest a potential use in treatment of acute uveitis.